-4(5y-6)-y=-3(y-4)

Simple and best practice solution for -4(5y-6)-y=-3(y-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(5y-6)-y=-3(y-4) equation:


Simplifying
-4(5y + -6) + -1y = -3(y + -4)

Reorder the terms:
-4(-6 + 5y) + -1y = -3(y + -4)
(-6 * -4 + 5y * -4) + -1y = -3(y + -4)
(24 + -20y) + -1y = -3(y + -4)

Combine like terms: -20y + -1y = -21y
24 + -21y = -3(y + -4)

Reorder the terms:
24 + -21y = -3(-4 + y)
24 + -21y = (-4 * -3 + y * -3)
24 + -21y = (12 + -3y)

Solving
24 + -21y = 12 + -3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3y' to each side of the equation.
24 + -21y + 3y = 12 + -3y + 3y

Combine like terms: -21y + 3y = -18y
24 + -18y = 12 + -3y + 3y

Combine like terms: -3y + 3y = 0
24 + -18y = 12 + 0
24 + -18y = 12

Add '-24' to each side of the equation.
24 + -24 + -18y = 12 + -24

Combine like terms: 24 + -24 = 0
0 + -18y = 12 + -24
-18y = 12 + -24

Combine like terms: 12 + -24 = -12
-18y = -12

Divide each side by '-18'.
y = 0.6666666667

Simplifying
y = 0.6666666667

See similar equations:

| 42y+4=16 | | 42y+4=17 | | 6.2m+3-1.9=-5.72 | | 8y=y+6+3 | | -(-(-k))-(-2)(-2+k)=-k-(4k+3) | | -2(6y-5)-y=-4(y-3) | | 15x+3=28+10x | | (5v+7)(5-v)=0 | | 8x+9=6x*15 | | -18-x=12 | | 0.63m=-3 | | -4(6y-8)-y=-4(y-3) | | -[3x+(3x+9)]=9-(4x+3) | | X-2+x-3+123=180 | | 2y+12=21 | | 44=-4v | | 3(x+1)+4=22 | | .4(x+.7)=.6x-4.2 | | 9-6y^2= | | 8+4p=10p-4 | | 10-4x=-32 | | 9k+4=22 | | 6-(b+2)= | | y-2=6x | | 25m+22=9m | | 6(2/3)-4(3/4)=1 | | -12=r+12 | | 7x-1=5+4x | | -5.5n+0.56=1.64 | | 2(x+9)=2-(x-9) | | 5(z-18)-30=6 | | 180-x=46(90-x) |

Equations solver categories